HPTLC method development and validation for simultaneous estimation of Metoprolol Succinate and Felodipine in bulk drugs and combined dosage forms. - JANHAVI R RAO, (International Journal of Pharma and Bio Sciences, 2018)
A combination of Metoprolol and felodipine tablet has achieved more pronounce antihypertensive. For this combination a simple, specific, accurate and precise HPTLC method has been developed for simultaneous determination of metoprolol succinate and felodipine in active pharmaceutical ingredient and tablet dosage form. Thin layer Chromatographic separation of the drugs was carried on aluminum plates precoated with silica gel 60 F254 as the stationary phase using chloroform: toluene: methanol: glacial acetic acid 6: 3: 1: 0.04 (v/v/v/v) as mobile phase. Densitometric evaluation was performed at 238 nm. The two drugs were resolved with RF values at 0.26 ± 0.02 and 0.53 ± 0.01 for Metoprolol succinate and Felodipine respectively. The validation parameters of method were performed as per ICH guidelines Q2A (R1). The linearity of method was seen in the range of 100-600 ng/spot and 10–60 ng/spot for Metoprolol succinate and Felodipine respectively. The % RSD for intraday precision was 1.15-1.76% of Metoprolol succinate, 1.03-1.23% of Felodipine and interday precision was 0.6-1.7 of Metoprolol succinate, 1.06-1.47% of felodipine. % recovery studies from tablets were in between 99.73 ± 0.70 % and 100.3 ± 0.06 % for Metoprolol succinate and Felodipine respectively. The developed method may be used for routine quality control analysis of Metoprolol succinate and Felodipine in active pharmaceutical ingredient and tablet dosage form.